2011
DOI: 10.1016/j.jcrs.2010.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment optical coherence tomography evaluation and comparison of main clear corneal incisions in microcoaxial and biaxial cataract surgery

Abstract: Although closure was reliable in both groups, the microcoaxial group had slightly fewer undesirable effects on the incision site. Low postoperative IOP seemed to be a significant factor in problematic healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 33 publications
3
42
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] To our knowledge, this is the first study to assess the longterm architectural features of CCIs using OCT. We found 3 posterior wound changes, 2 of which were seen only in the first 3 months following surgery. Descemet detachment was seen in 37.1% of corneas 1 day postoperatively and in no eye imaged after 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] To our knowledge, this is the first study to assess the longterm architectural features of CCIs using OCT. We found 3 posterior wound changes, 2 of which were seen only in the first 3 months following surgery. Descemet detachment was seen in 37.1% of corneas 1 day postoperatively and in no eye imaged after 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, they could also be attributable to differences in technique in imaging these incisions. Fourier-domain OCT was used in our study and the study by Can et al, 11 and spectral-domain OCT was used in all other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical developments now allow phacoemulsification to be performed using a biaxial or microcoaxial approach. 1,2 Recent advances in IOL technology and the use of cartridge systems allow IOL implantation in the capsular bag through small corneal incisions.…”
mentioning
confidence: 99%
“…Optical coherence tomography studies of clear corneal incision wound architecture I would like to congratulate Can et al 1 on their comparative study of the optical coherence tomography (OCT) appearance of clear corneal incisions (CCIs) in cataract surgery, particularly their demonstration of the detrimental effects of enlarging the wound at the end of surgery. It has been suggested that CCIs are most vulnerable in the immediate postoperative period, when they are susceptible to microleaks causing a decrease in intraocular pressure (IOP).…”
mentioning
confidence: 99%